2010
DOI: 10.1593/neo.10526
|View full text |Cite
|
Sign up to set email alerts
|

Long-term In Vitro Treatment of Human Glioblastoma Cells with Temozolomide Increases Resistance In Vivo through Up-regulation of GLUT Transporter and Aldo-Keto Reductase Enzyme AKR1C Expression

Abstract: Glioblastoma (GBM) is the most frequent malignant glioma. Treatment of GBM patients is multimodal with maximum surgical resection, followed by concurrent radiation and chemotherapy with the alkylating drug temozolomide (TMZ). The present study aims to identify genes implicated in the acquired resistance of two human GBM cells of astrocytic origin, T98G and U373, to TMZ. Resistance to TMZ was induced by culturing these cells in vitro for months with incremental TMZ concentrations up to 1 mM. Only partial resist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
74
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 109 publications
(77 citation statements)
references
References 55 publications
2
74
1
Order By: Relevance
“…[4][5][6] Consistent with this observation, we show that a few number of GBM primary cultures display growth inhibition in response to TMZ. Likewise, among 6 GBM-derived cell lines examined, 3 are shown to be TMZ-responsive.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…[4][5][6] Consistent with this observation, we show that a few number of GBM primary cultures display growth inhibition in response to TMZ. Likewise, among 6 GBM-derived cell lines examined, 3 are shown to be TMZ-responsive.…”
Section: Discussionsupporting
confidence: 78%
“…Indeed, GBMs can present innate resistance or develop acquired resistance during TMZ treatment. [4][5][6] Resistance of GBMs to TMZ is reported to be mainly, but not exclusively, dependent on high levels of the DNA repair enzyme, O 6 -methylguanine methyltransferase (MGMT), which can reverse the methylation damage induced by alkylating agents. [7][8][9] Although a number of studies have shown that a deficiency of MGMT can augment the sensitivity of GBMs to alkylating agents such as TMZ, a panel of tumors with low levels of MGMT are nevertheless chemoresistant.…”
Section: Introductionmentioning
confidence: 99%
“…While cancer cells express all 4 of these GLUTs, GLUT3 may be the predominant one in cancers such as glioblastoma (22), where it has been associated with aggressive aspects of cancer such as the epithelial to mesenchymal transition (23) and the tumor-initiating stem cells of glioblastoma (24). Interestingly, GLUT3 overexpression has also been described in temozolomide-resistant glioblastoma cell lines established in culture (25). Further work will also be needed to define whether the glycosylated versus nonglycosylated forms of GLUT3, both of which were detected in our study, serve different functional roles in the context of resistance to antiangiogenic therapy, as has been suggested for GLUT1 for some tumor cells in the absence of therapeutic stressors (26).…”
Section: Discussionmentioning
confidence: 99%
“…If o-quinones and the ROS they generate are not eliminated, they can potentially cause covalent and oxidative DNA lesions, increasing the mutational load of PAH-exposed cells. Together, this sequence of events may contribute to PAH-induced oral carcinogenesis and other malignancies [15,23,25,[53][54][55]58,59,62].…”
Section: Discussionmentioning
confidence: 99%
“…They are monomeric intracellular enzymes that catalyze the conversion of aldehydes and ketones to their corresponding alcohols by utilizing NADH and/or NADPH as cofactors, and bind bile acid with high affinity. Their enzymatic activities play crucial roles in balancing malignant transformation, cancer progression, and response to cytotoxic therapies [25,[52][53][54][55].…”
Section: Discussionmentioning
confidence: 99%